Soluble Fraction of Trichosanthes diocia Peroxidase in Decolorization of Reactive Orange 15 - Prabhash K Pandey, Farrukh Jamal*, Tabish Qidwai and (Journal of Ecobiotechnology, 2010)
<span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">Salt fractionated proteins from Trichosanthes diocia was used to study decolorization of Reactive Orange 15 under multifarious experimental conditions like pH, temperature, time interval, enzyme concentration and in the presence of redox mediator 1-hydroxybenzotriazole (HOBT)/ vanillin. T. diocia peroxidase showed extensive decolorization of Reactive Orange15 in the presence of 1-hydroxybenzotriazole (HOBT) / vanillin. The dye was decolorized effectively with HOBT and so further studies were performed in the presence of HOBT.Â At an enzyme concentration of 0.45 EUmL-1 the peroxidase was able to remove the reactive dye up to a maximum of 94.6% with 1.0 mM 1-hydroxybenzotriazole. Maximum decolorization was achieved at a temperature of 40Â°C, pH 5.0 and with an incubation period of 90 min. Thus, the data indicates that T. diocia peroxidase could be a potential source for developing an inexpensive and efficient method for the treatment of recalcitrant Reactive Orange15 dyes that are potentially toxic. <span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">— <span style="line-height: 110%; font-family: ";Garamond";,";serif";; font-size: 10pt; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;"> Department of Biochemistry (DST-FIST & UGC-SAP Supported), Dr. Ram Manohar Lohia Avadh University, Faizabad-224001, U.P. (India) — Please Cite This Article As: Â Farrukh Jamal, Tabish Qidwai and Prabhash K Pandey. 2010. Soluble Fraction of Trichosanthes diocia Peroxidase in Decolorization of Reactive Orange 15. J. Ecobiotechnol. 2(5):36-41. Â